All the president's money : investigating the secret foreign schemes that made the Biden family rich - Comer, James, 1972- (HarperCollins Publishers, 2024)
"He shared a bookkeeper with Hunter Biden, and a law firm with several Biden family members that managed their money. Hunter, who hasn’t had a real job in decades, has raked in tens of millions of dollars. Joe Biden met many of the foreigners writing the checks, but still maintains all of these situations are nothing to be concerned about. In All the President’s Money, Congressman James Comer takes readers on a captivating journey through the murky world of the Biden family’s business dealings. This explosive exposé delves deep into allegations of corruption, influence peddling, and money laundering. If no one else goes to prison, it will only be because of abuse of power. None of this makes sense if you only have the network news to go on. If the Bidens had been involved in money laundering schemes, wouldn’t the banks have noticed? They noticed unusual activity, and they filed scores of “Suspicious Activity Reports.” Wouldn’t law enforcement have done something about it? Several of Hunter Biden’s domestic and foreign business associates are currently in prison. Hasn’t the Burisma thing blown over? That was only one of many seven-figure deals they cooked up. Surely poor recovering addict Hunter Biden hasn’t admitted to most of this? But he has. Through meticulous research and insider access, All the President’s Money uncovers the truth about the Biden family’s shady finances, from China to Ukraine, Russia to Hollywood, following the money trail every Democrat insists doesn’t exist." -- Publisher annotation.